Interpretive Paradigm on Development of Science and Accounting Research - Muhammad Adil; Nadhirah Nagu; Andi Rustam; Wahyuni; Idrawahyuni; Endang Winarsih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to understand the reality of social life in depth by understanding its essential nature through the level of emotional experience or subjective experience. With different levels of understanding and human behavior as subjects, research with this paradigm is not looking for generalizations. The interpretive paradigm is considered to have a correlation relationship with problems in the study of accounting and social science so that it can be used as a scientific approach in accounting development. This type of research uses qualitative. The research approach uses a literature review with several sources from previous research. The results of this study indicate that the interpretive paradigm in the philosophy of science can help researchers to see further and deeply related to the reality of social life, so that they can determine whether the reality is just a symbol and the ideas that arise are a truth about the reality of the problem. With the latest information generated will provide the development of science that is getting closer to the truth about the science being studied. In addition, as a perspective in interpretive sociology approach is a solution in solving an accounting problem that has a relationship with social interaction where an in-depth study is carried out and can affect the development of accounting science.